PENGARUH KEPEMIMPINAN DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUPANG - Sitorus, Detson Ray Halomoan; Agustian, Dimas; Huda, Nurul; Sitorus, Folwem Hatorangan (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2022)
Performance at the Department of Population and Civil Registration of Kupang Regency did not reach the target. Employee performance control by organizational leadership and communication. This research aims to assess the effect of leadership and organizational communication on employee performance. This research uses explanatory research that explains the causal relationship between variables through hypothesis testing. The population at the Department of Population and Civil Registration of Kupang Regency is 33 employees. The sampling in this research used the saturated sample technique. The data collection method used is a questionnaire by distributing directly to the Department of Population and Civil Registration of Kupang Regency. The data acquired is then analyzed quantitatively using multiple linear regression analysis. The consequences of this research indicate that leadership and organizational communication have a simultaneous positive and significant effect on employee performance. Other results show that leadership and organizational communication have positive and significant effects on employee performance partially. Leadership and organizational communication in organization need to develop to improve employee performance.